(untitled) (Revista Rupturas, 2026)
This text is the result of research focused on women vendors of medicinal plants in three markets and two open-air markets in the city of Chetumal, Quintana Roo, Mexico. It offers a critical reflection on care work and healing, exploring how these practices and knowledge have found visibility in diverse contemporary settings. The text is structured in four sections: a theoretical framework, materials and methods used, results, and main findings. The findings were analyzed in three axes of analysis: the relationship between care and healing and the appropriation and defense of territory; the timing and rhythms of their daily activities; and the relationships and bonds the women establish to heal and care.